2015
DOI: 10.4238/2015.may.4.8
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the promoter region of let-7 family is associated with lung cancer risk in Chinese

Abstract: ABSTRACT. Lung cancer is a complex polygenic disease and many genetic factors are involved in the development of the disease. As one of the most important and widely studied families of microRNA, let-7 appears to play an important role in initiation and progression of lung cancer. Any small changes in miRNA level or its target point can cause significant changes in gene function. In this study, we examined whether a single-nucleotide polymorphism in the promoter region of the let-7 family (rs10877887) is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…More recently, Shen et al (2015) reported that the single-nucleotide polymorphism in the promoter region of let-7 family is strongly associated with susceptibility to lung adenocarcinoma in Chinese individuals, especially in females who are more than 60 years old. In addition, aberrant expression of let-7 has also been observed in many other human malignancies (Ma et al, 2014), with a distinct expression pattern in cancer development (Boyerinas et al, 2010;Wagner et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Shen et al (2015) reported that the single-nucleotide polymorphism in the promoter region of let-7 family is strongly associated with susceptibility to lung adenocarcinoma in Chinese individuals, especially in females who are more than 60 years old. In addition, aberrant expression of let-7 has also been observed in many other human malignancies (Ma et al, 2014), with a distinct expression pattern in cancer development (Boyerinas et al, 2010;Wagner et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al demonstrated that the let7a‐2 rs10877887 polymorphism might be associated with a lower risk of PTC and the rs13293512 polymorphism could be correlated with lymph node metastasis in patients with PTC . In addition, several reports have described the association between let‐7 family polymorphisms and different cancers, such as head and neck cancer, hepatocellular carcinoma, and lung cancer …”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of let-7 on cancer and its mechanism involves a number of processes, SNPs are believed to play a prominent role in all. Two SNPs identified in the promoter region of let-7 have been associated with hepatocellular carcinoma and lung cancer susceptibility (Shen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%